PENGARUH LAMA PENYIMPANAN TELUR HERBAL AYAM RAS FASE PERTAMA PADA SUHU RUANG TERHADAP PENURUNAN BERAT TELUR, DIAMETER RONGGA UDARA, DAN INDEKS ALBUMEN - Reza Fahlevi; Dian Septinova; RR Riyanti; Khaira Nova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the effect and the best of storage time for first phase herbal chicken eggs at room temperature at an average of 29,3°C on the decrease in egg weight, air cavity diameter, and albumen index. This research was conducted on 7 October–4 November 2020 at the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a completely randomized design method (CRD) with 5 treatments of egg with storage time for 0, 1, 2, 3, 4 weeks and 4 replication. The data obtained were tested according to analysis of variance and tested with the Least Significant Difference (LSD) test at the 5% real level. The results of this study showed that the herbal egg storage treatment had a significant effect (P <0.05) on reducing egg weight, air cavity diameter, and index albumen. Storage time of 1 week at room temperature with an average of 29,3°C gave the best effect on the lowest egg weight, namely 1.31% ± 0,14, the width of air cavity diameter of 1.897 ± 0,255 cm, and albumen index of 0.055 ± 0,007 when compared to storage time of 2, 3, and 4 weeks. Keywords: herbal egg, room temperature, egg weight loss, air cell diameter,and albumen index.